The Time Warner and AOL merger - Albuquerque, Hélder Salvador de (2011)
The corporate world has experienced Merger movements since the beginning of the XX century when the first wave of Mergers & Acquisitions occurred. These Merger movements always represent intent from companies to take advantage of existing market opportunities or leverage the competitive position of the combined company, always with the final objective of creating value for the shareholders. The Merger between Time Warner and AOL occurred in 2000 and represented the combination of a Media and Entertainment Conglomerate (Time Warner) with a company operating in the Internet segment (AOL) that was experiencing some outstanding growth. The present Case Study tries to firstly identify the situation of the Media and Entertainment Market and its major segments at the time of the Merger, including the positioning of both companies as well as its motivations to merge. The terms of the deal are analyzed through a Free Cash Flow to the Firm (FCFF) valuation of both companies at the time of the Merger that leads to the conclusion that they were overvalued and the price paid was too high. The Merger analysis was complemented with a Market Multiples overview of both companies and an assessment of the Stock Market reaction on the announcement of the Merger that showed the lack of ability of the Market to take a clear view of the full impact of this M&A movement.